Maize growth in nutrient solution with aluminum - Techio, Jeonice Werle; Escosteguy, Pedro Alexandre Varella; Berres, Diego; Zanella, Silas (Revista de Ciências Agroveterinárias, 2012)
The use of aluminum (Al) tolerant hybrids is an important factor to corn production on acid soils. The objective was to assess the reaction of maize hybrids according to excessive activities of Al in solution under a plastic greenhouse. Plants of Pioneer 30F53 (early) and Pioneer 32R48 (super early) hybrids were grown in pots with nutrient solution containing 0.0, 5.81, 9.9, 15.0, 21.0 and 29,0 μmol L-1 of Al activities, at pH 4.5. These activities corresponded to the following Al concentrations: 0.0, 0.50, 0.75, 1.00, 1.25 and 1.50 mmol L-1, respectively. A randomized block design was used with four replications. Treatments were arranged in a bifactorial model, where hybrids were combined with the Al activity. After three weeks of growth, the study assessed the root length, the dry weight of root system and shoot, the number of secondary roots, the content of Al in the plant and its toxic activity that suppresses 10% of the value of the attributes assessed. The interaction of the factors studied did not influence the variables assessed. The increase of Al activities in solution up to 29 μmol L-1 reduced the seminal root length and the dry weight of the roots and shoot in a linear way. The Hybrid 32R48 was more tolerant to Al.